Procurement by international organizations : a global administrative law perspective / Elisabetta Morlino. - Morlino, Elisabetta (Cambridge University Press, 2019)
How do international organizations procure goods, services and works to carry out their institutional mission? How does this procurement activity affect individuals? Does the procurement relationship between international organizations and private subjects bring an even distribution of rights and duties? Are international organizations accountable to private subjects and states when allocating their resources through procurement? The book explores the complex phenomenon of procurement by international organizations from the point of view of the relationship between international organizations and private subjects. It provides, for the first time, a systematization and conceptualization of the emerging rules and practices of procurement by international organizations. It also identifies the international political dynamics and interplay of interests underlying these rules and practices. In doing so, it shows how these dynamics shape the exercise of international public authority over private subjects, and the scope of private subjects' rights vis-à-vis international organizations.